Strategi Pemasaran Air Minum dalam Kemasan di Pondok Pesantren Riyadhus Samawi - Dwi Wahyu Ningtyas; Nuhan Nabawy; Ariska Rizkyani (Lembaga Pengembangan Kinerja Dosen, 2024)
In general, some of the community's drinking water needs can be sourced from well water and water that has been treated by the Regional Drinking Water Company (PDAM). However, the increasing demand for drinking water sometimes cannot be met by well water sources or water that has been treated by PDAM. Along with technological advances, accompanied by increasingly busy community activities today tend to choose a more practical way at a relatively low cost in meeting drinking water needs. One of the alternative ways to fulfill drinking water needs is by using mineral water products. Marketing is a process of preparing integrated communication that aims to provide information about goods or services in relation to human needs. The marketing carried out at the Riayadus Samawi Islamic Boarding School is still very simple, namely from word of mouth to the congregation. So that Yarisa Drinking Water has not been sold widely like bottled drinking water in general because the majority of consumers are still worshipers and the neighborhood around the cottage. The purpose of this community service is to contribute thoughts and training, especially to the manager of Yarisa drinking water regarding the importance of analyzing marketing strategies for a company in an effort to market its products so that these products can be accepted by the public and distributed widely. The PKM process carried out at the Riyadus Samawi Ludoyo Blitar Islamic Boarding School consists of three stages, including: first, problem identification with a study carried out by the PKM team, Yarisa drinking water managers, cottage administrators, cottage caregivers, and cottage owners to find out the quality and development of Yarisa drinking water marketing strategies. The second stage is the implementation of PKM by holding a seminar with the theme “Marketing Strategy for Bottled Drinking Water at Riyadus Samawi Islamic Boarding School” and attended by Yarisa drinking water managers and students and board members. The third stage is monitoring and evaluation of whether the bottled drinking water marketing strategy delivered by the PKM team has been implemented in Yarisa drinking water. The results of this PKM are socialization and assistance regarding bottled drinking water marketing strategies and making several marketing and motivational programs so that in the future Yarisa drinking water owned by Riyadus Samawi Islamic Boarding School can be marketed widely.